KNOWLEDGE BASED HRM PRACTICES,INTELLECTUAL CAPITAL DAN INOVATION - Yeni Fajariyanti; Anastasia Riani Suprapti (Universitas Lambung Mangkurat, 2020)
This paper purposes is for identify about knowledge-based human resource management practice to innovation performance with firm's intellectual capital at manufactures and services firm in Surakarta. This reserach used purposive technique sampling. The result is intellectual capital which is human capital, structural capital and relational capital are positive mediated knowledge-based human resource management practice to innovation performance.